Radiography Hystero Salpingography (HSG) With the Allegation of Nonpatency of Both Fallopii Tubes at Columbia Asia Hospital Medan - Simamora, Djamiandar; Ariyanti, Stephanie (PT Inovasi Pratama Internasional, 2023)
Hystero Salpingography (HSG) radiography with suspected non-patency of both fallopian tubes at the Radiology Installation of Columbia Asia Hospital, Medan. Scientific Writing for the Diploma III Radiodiagnostic Engineering and Radiotherapy Study Program Sinar Amal Bhakti Foundation Medan 2021. Hystero Salpingography (HSG) is an examination of the uterus and salpinx using radio opaque contrast media via a uterine canule carried out by a radiologist with the patient supine on the flouroscopy table, examination This can also be done with conventional radiography using a tube from above. Non-patent tubes are tubes that are occluded so that sperm cannot reach the ampulla to fertilize the ovum. The aim of the examination is to show the anatomy and abnormalities accurately by means of contrast injection using a catheter. This research was conducted at the Radiology Installation at Columbia Asia Hospital, Medan. The examination technique uses an antero-posterior projection which aims to optimally show the anatomical structure of the uterus and fallopian tubes. The aircraft used in this research is a Philips Pesawar General X-ray Unit with the Bucky Diagnost CS.Optimus 80 type and a capacity of 500 mA. The cassette used measures 18x24 cm. The film processing process used is Computed Radiography (CR).